The thromboelastometric discrepancy between septic and trauma induced disseminated intravascular coagulation diagnosed by the scoring system from the Japanese association for acute medicine. Issue 31 (August 2016) - Koami, Hiroyuki; Sakamoto, Yuichiro; Sakurai, Ryota; Ohta, Miho; Imahase, Hisashi; Yahata, Mayuko; Umeka, Mitsuru; Miike, Toru; Nagashima, Futoshi; Iwamura, Takashi; Yamada, Kosuke Chris; Inoue, Satoshi
Abstract : Abstract: The aim of this study is to evaluate the hematological differences between septic and traumatic disseminated intravascular coagulation (DIC) using the rotational thromboelastometry (ROTEM). This retrospective study includes all sepsis or severe trauma patients transported to our emergency department who underwent ROTEM from 2013 to 2014. All patients were divided into 2 groups based on the presence of DIC diagnosed by the Japanese Association for Acute Medicine (JAAM) DIC score. We statistically analyzed the demographics, clinical characteristics, laboratory data, ROTEM findings (EXTEM and FIBTEM), and outcome. Fifty-seven patients (30 sepsis and 27 severe trauma) were included in primary analysis. Sepsis cases were significantly older and had higher systemic inflammatory response syndrome (SIRS) scores, whereas there were no significant differences in other parameters including Acute Physiology and Chronic Health Evaluation (APACHE) II score, sequential organ failure assessment (SOFA) score. Twenty-six patients (14 sepsis and 12 severe trauma) were diagnosed with DIC. The Septic DIC (S-DIC) group was significantly older and had higher DIC scores than the traumatic DIC (T-DIC) group. Hematologic examination revealed significantly higher CRP, fibrinogen, lower FDP, DD, and higher FDP/DD ratio were found in the S-DIC group in comparison with the T-DIC group. ROTEM findings showed that the A10, A20, and MCF in the FIBTEM test were significantly higher in the S-DIC group. However, no statistical differences were confirmed in the LI30, LI45, and ML in EXTEM test. The plasma fibrinogen level and fibrinogen based clot firmness in whole-blood test revealed statistical significance between septic and traumatic DIC patients.